Biodiversity conservation in productive forest landscapes - Nasi, Robert (Oxford-IBH, 2001)
An attemps to pursue biodiversity objectives in both proteced areas and in production forests have often failed because the attribution of costs and benefits was unfair and regulations proved unenforceable. Most people would agree that biodiversity is most likely to be maintained if local benefits are maximised and local costs are minimised. The author argues that various sorts of multiple-use forests are likely to be the best option for biodiversity conservation in many situations where poor people live in proximity to forests rich in biodiversity. It is inevitable that timber extraction will be a major element of this multiple-use in many forest areas. This paper further argues that there are no fundamental technical obstacles to meeting many biodiversity objectives in forests managed for timber. The diversity of forests and people who depend upon them is so great that it is neither desirable nor possible to develop broadly generalised prescriptions for management. The extent of the trade-offs in reconciling global and local values is such that even with optimal management arrangements some form of compensation or subsidy to forest-dependent stakeholders will often be unavoidable.